Teaching compassion through a community-led, experiential learning activity for undergraduate medical students: the Empathy Project (Canadian Medical Education Journal, 2025)
Implication StatementWe co-facilitated a mandatory community-led experiential learning activity for medical students with the Alliance to End Homelessness Ottawa that demonstrates the feasibility and positive impact of incorporating community-led learning into the medical school curriculum.